2016
DOI: 10.5114/reum.2016.63662
|View full text |Cite
|
Sign up to set email alerts
|

Secretory activity of subcutaneous abdominal adipose tissue in male patients with rheumatoid arthritis and osteoarthritis – association with clinical and laboratory data

Abstract: IntroductionAdipose tissue exerts widespread effects on the metabolism and immune system, but its activity differs between the genders. In the general population low-grade adipose tissue inflammation contributes to development of diseases of affluence. Little is known about the systemic impact of peripheral fat tissue in osteoarthritis (OA) and rheumatoid arthritis (RA), characterized by chronic, low- and high-grade systemic inflammation, respectively. To clarify this we evaluated the secretory activity of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
(52 reference statements)
1
8
0
1
Order By: Relevance
“…Moreover, some [21, 30], but not all [22, 31], studies have demonstrated that anti-TNF-α therapy in RA was associated with an increase in serum adiponectin levels. A few studies suggested that the level of serum adiponectin in RA is related to disease duration [15, 32]. In this respect, we have observed that serum adiponectin levels correlated with CRP only in patients with RA duration ≥ 8 years.…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, some [21, 30], but not all [22, 31], studies have demonstrated that anti-TNF-α therapy in RA was associated with an increase in serum adiponectin levels. A few studies suggested that the level of serum adiponectin in RA is related to disease duration [15, 32]. In this respect, we have observed that serum adiponectin levels correlated with CRP only in patients with RA duration ≥ 8 years.…”
Section: Discussionsupporting
confidence: 48%
“…Besides serum levels, synovial fluid concentrations of adiponectin are increased in RA [17,71]. In RA patients, subcutaneous abdominal adipose tissue has been found to secrete more adiponectin compared to subcutaneous abdominal adiposetissue from OA patients, and the amount of adiponectin secreted from this tissue positively correlated with the 28-joint disease activity score (DAS28) and disease duration [72].…”
Section: Adiponectinmentioning
confidence: 99%
“…In humans, ScAT of the abdomen, often described as subcutaneous abdominal adipose tissue (SAAT), is routinely subjected to medical examination. SAAT explants stimulated with IL-1b could significantly produce high levels of pro-and antiinflammatory cytokines in patients with OA 15 , suggesting that SAAT could contribute to the inflammatory pathogenesis of knee OA. Furthermore, excessive SAAT may also increase knee joint loading and impulse 16 , indicating that it may also cause knee OA through biomechanical mechanisms.…”
Section: Subcutaneous Adipose Tissuementioning
confidence: 99%